Proceedings 20th IEEE International Parallel &Amp; Distributed Processing Symposium 2006
DOI: 10.1109/ipdps.2006.1639560
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous zero-copy communication for synchronous sockets in the sockets direct protocol (SDP) over InfiniBand

Abstract: Sockets Direct Protocol (SDP) is an industry standard pseudo socketslike implementation to allow existing sockets applications to directly and transparently take advantage of the advanced features of current generation networks such as InfiniBand. The SDP standard supports two kinds of sockets semantics, viz., Synchronous sockets (e.g., used by Linux, BSD, Windows) and Asynchronous sockets (e.g., used by Windows, upcoming support in Linux). Due to the inherent benefits of asynchronous sockets, the SDP standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…The authors found that improvements could be made to throughput for larger message sizes. We subsequently introduced an asynchronous zero-copy mechanism [1] providing better performance than that obtained by Goldenberg et al…”
Section: Related Workmentioning
confidence: 99%
“…The authors found that improvements could be made to throughput for larger message sizes. We subsequently introduced an asynchronous zero-copy mechanism [1] providing better performance than that obtained by Goldenberg et al…”
Section: Related Workmentioning
confidence: 99%
“…Due to the inherent benefits of asynchronous sockets, the SDP standard also allows several intelligent approaches such as source-avail and sink-avail based zero-copy for these sockets. However, most of these approaches that work well for the asynchronous sockets interface are not as beneficial for the synchronous sockets interface [4]. Further, due to its portability, ease of use and support on a wider set of platforms, the synchronous sockets interface is the one used by most sockets applications today.…”
Section: Communication Protocol Supportmentioning
confidence: 99%
“…In our approach, the key idea in meeting these design goals is to memory-protect the user buffer (thus disallow the application from accessing it) and to carry out communication asynchronously from this buffer, while tricking the application into believing that we are carrying out data communication in a synchronous manner. More details about the design of the AZ-SDP scheme can be found in [4].…”
Section: Communication Protocol Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Zero copy protocols [3,27] and remote memory access techniques [19] have been added to Ethernet interfaces in order to improve latency. Also, the addition of an on/off based flow-control mechanism to the Ethernet standard in 1997 [24], allows Ethernet to behave as a loss-less network [21] without the need for expensive retransmission and acknowledgement of packets.…”
Section: Introductionmentioning
confidence: 99%